Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
Your solution is (-1, 0)
Step-by-step explanation:
3x - y = -3
x + y = -1
The elimination method eliminates one variable at a time to find the other variable.
Here we can see that the y variable will naturally be eliminated.
3x - y = -3
x + y = -1
--------------
4x = -4
Divide both sides by 4 to isolate x.
x = -1
Now plug this value back into one of the equations.
3(-1) - y = -3
Multiply.
-3 - y = -3
Add 3 to both sides.
-y = 0
Divide both sides by -1.
y = 0
Your solution is (-1, 0)
Check this solution by plugging these values into the second equation.
-1 + 0 = -1
-1 = -1
Your solution is correct.
Hope this helps!
Answer:
x = -1
y = 0
Step-by-step explanation:
3x - y = -3 -------------------(I)
x + y = -1 ------------------(II)
Add equation (I) & (II). Now, y will be eliminated and you can find the value of x
(I) 3x - y = -3
(I) x + y = -1
4x = -4
x = -4/4
x = -1
Plugin x = -1 in equation (II)
-1 + y = -1
y = -1 +1
y = 0
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.